2005
DOI: 10.1111/j.1399-0012.2005.00358.x
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the donor pool: use of renal transplants from non‐heart‐beating donors supported with extracorporeal membrane oxygenation

Abstract: In response to organ shortage, we used the renal grafts from non-heart-beating donors (NHBDs). Extracorporeal membrane oxygenation (ECMO) was used to maintain NHBDs before organ procurement. We compared the results of renal transplantation from different donors, including heart-beating donors (HBDs), living-related donors (LDs), and NHBDs supported with ECMO. From February 1998 to June 2003, we recruited 219 patients receiving renal transplantation at National Taiwan University Hospital. Among them, 31 receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 16 publications
0
37
0
4
Order By: Relevance
“…Eight studies (10 -12, 14, 17, 18, 21, 24) reported in situ cooling as the method of kidney preservation. Lee et al (16) used extracorporeal membrane oxygenation to decrease warm ischemic injury to the kidneys. Pokorny et al (19) did not have the need for in situ flush because of different legislation, which allowed them to proceed with renal procurement as soon as cardiac death was established.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies (10 -12, 14, 17, 18, 21, 24) reported in situ cooling as the method of kidney preservation. Lee et al (16) used extracorporeal membrane oxygenation to decrease warm ischemic injury to the kidneys. Pokorny et al (19) did not have the need for in situ flush because of different legislation, which allowed them to proceed with renal procurement as soon as cardiac death was established.…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of DGF and PNF was reduced after normothermic recirculation compared to standard in situ or total body cooling. Gravel et al described a DGF rate of 11% in controlled DCD donors [92] and Lee et al found similar 5 year graft survival rates to DBD and living donors [93]. Maintaining circulation before retrieval is thought to condition the organs by up-regulating adenosine receptors which may protect against preservation injury [91].…”
Section: Normothermic Machine Perfusionmentioning
confidence: 99%
“…Similarly, in the Henry Ford Health System (11) and at Wake Forest University (2), ECMO cannulas are inserted premortem, after informed consent. At National Taiwan University Hospital, the insertion of ECMO cannulas is conducted postmortem (9), with no mention of the requirement for informed consent.…”
Section: Consentmentioning
confidence: 99%
“…Only a few cDCDD centers, however, have reported the use of extracorporeal membrane oxygenation (ECMO) to improve future graft outcome, including National Taiwan University Hospital, Taiwan (9); the University of Michigan, Ann Arbor, Michigan (10); the Henry Ford Health System, Detroit, Michigan (11); Wake Forest University, WinstonSalem, North Carolina (2); and three centers (Cambridge, Birmingham, and Edinburgh) in the United Kingdom (12).…”
Section: Introductionmentioning
confidence: 99%